The Structure of Worker Compensation in Brazil, with a Comparison to France and the United States - Menezes-Filho, Naércio Aquino; Muendler, Marc-Andreas; Ramey, Garey (The Review of Economics and Statistics, 2008)
We employ a comprehensive linked employer-employee data set for Brazil to analyze wage determinants and compare results to Abowd, Kramarz, Margolis and Troske (2001) for French and U.S. manufacturing. While returns to human capital variables in Brazilian manufacturing exceed those of the other countries, occupation and gender differentials are similar. The worker characteristics component of individual compensation accounts for much of the greater wage inequality in Brazil, but the establishment-fixed component has scant explanatory power. Thus, firm- or industry-level factors have little scope for explaining the differences in wage inequality. Brazil's wage structure closely resembles that of France, a country with some similarity in labor-market institutions.